A System Usability Scale for Development of YouTube API-based E-Learning Module - Ahda, Handika Naufal; Purbohadi, Dwijoko; Alamsyah, Nurwahyu (Emerging Information Science and Technology, 2023)
E-learning is formal and non-formal learning carried out using technology, allowing students and teachers to conduct teaching and learning processes using electronic media. By using the e-learning module, YouTube can be included to create material and to ease learning. However, a lot of educational videos on YouTube cover ground already well-covered. Accordingly, the audience cannot skip unnecessary things. Therefore, a YouTube API-based e-learning module was built to help users learn the material effectively. A System Usability Scale (SUS) was employed in this study, allowing easier data collection using a questionnaire. The data analysis acquired a score of 68 (B), signifying the usefulness of the module. The module provided convenience to the users to grasp the material in a brief time.